Etika dalam Penggunaan Media Sosial: Perilaku Komunikasi yang Bertanggung Jawab - Muzaki, Didy; Nasichah, Nasichah; Hudan Raya, Muhammad; Fatiyah, Nahda; Irma Damayanti, Nilam (Universitas Gajah Putih, 2023)
This research contains the understanding of people who have social media regarding ethical actions in using social media. This study aims to determine the public's understanding of ethics in the responsible use of social media. This study uses a quantitative method by filling out a questionnaire through the Google form. The results of the data are seen from the answers contained in the questionnaire using theory from previous books and journals.